The Role of Salafiyah Pesantren in Fostering the Character and Morality of Youth: A Case Study at Al Fatah 1 Singosari Malang - Qomariyah, Siti Lailatul; Husni, Muhammad (Pelangi (e-Journal), 2025)
This study explores the strategic role of "salafiyah" Islamic boarding schools (pesantren) in shaping the character and moral foundation of the younger generation, focusing on a case study at Pondok Pesantren Al Fatah 1 Singosari, Malang. In the face of globalization and the erosion of traditional values, pesantren offer a distinctive educational model that integrates religious learning with character development. Through traditional teaching methods such as "sorogan", "bandongan", and "musyawarah", as well as daily collective life practices, pesantren instill values of discipline, humility, respect, and responsibility. The use of classical Islamic texts ("turats") enhances not only religious knowledge but also spiritual depth and ethical conduct. Moreover, the exemplary leadership of Kyai Farihin Muhsan and the family of "ndalem"(kyai’s household) serves as a living model for santri, reinforcing values through daily interactions filled with respect, empathy, and consistency. This study concludes that "salafiyah" pesantren, with their balanced emphasis on religious, cultural, and practical values, play a vital role in preparing morally upright and resilient individuals in the modern era.